Leniency Policies in the Prosecution of Economic Crimes and Corruption Consensual Justice and Search for Truth in Brazilian and German Law - Schertel Mendes, Francisco (Schriften zum Internationalen und Europäischen Strafrecht,, 2021)
Die Arbeit beinhaltet eine kritische Untersuchung des Einsatzes der Kronzeugenregelung in Brasilien. Im Rahmen eines Rechtsvergleichs mit dem deutschen Recht sowie einer empirischen Analyse der brasilianischen Praxis wird gezeigt, wie der Gebrauch der Kronzeugenregelung grundlegende Garantien des brasilianischen Strafprozessrechts unterwandert. Unter Rückgriff auf wirtschaftswissenschaftliche Literatur werden zudem ernstzunehmende, negative Externalitäten festgestellt. Die Arbeit kommt zu dem Schluss, dass der Einsatz solcher Methoden einer Privatisierung des Ermittlungsverfahrens und der Strafverfolgung gleichkommt. Die Verknüpfung der Kronzeugenregelung mit dem Ideal einer "konsensualen Justiz" wird abgelehnt. Abstract Based on empirical research, the book develops a critical analysis of the use of leniency policies in Brazil. Drawing on a comparative perspective with German Law, the book shows how the current practice of leniency policies in Brazil jeopardizes fundamental guarantees of criminal procedure. The book also draws on a growing body of economic literature to assert that leniency agreements have serious - albeit unnoticed - side effects and may lead to significant negative externalities. The book rejects the association of leniency policies with the ideal of "consensual justice" and affirms that these mechanisms represent a form of privatization of investigative and prosecutorial activities, exploring the expectations and risks of this process.